Question:
Write each of the following equations in y = mx + b form
Solution:
1) Let the equation
![2y=\text{ -1x-8}](https://img.qammunity.org/2023/formulas/mathematics/college/9yqf8lvx3tvdmo6cq4r4wk3ro0xs6f6t1l.png)
Dividing both sides of the equation by two, we have that this is equivalent to:
![y\text{ = }(-1)/(2)x-(8)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/gfv54nxenaz4ggq42ie6aqg5181xoovk7q.png)
this is equivalent to:
![y\text{ = }(-1)/(2)x-4](https://img.qammunity.org/2023/formulas/mathematics/college/g0mycsxgfeupzizk0wkxl05fhij6v2v6lo.png)
Then the above equation is in the form y = mx +b.
2) Consider the following equation:
![y-4\text{ = -3(x-3)}](https://img.qammunity.org/2023/formulas/mathematics/college/1fk99inzspu5l40ebbealw9cyy8s34nf5z.png)
adding to both sides of the equation the number 4, we get:
![y\text{ = -3(x-3) + 4}](https://img.qammunity.org/2023/formulas/mathematics/college/i778q9owsbel2pa9xzp7biuq9dsj13yura.png)
now, using the distributive property, we get:
![y\text{ = -3x+9 + 4}](https://img.qammunity.org/2023/formulas/mathematics/college/cc8hiii9f23cdbqdtu64wvd1j3vlvlidbv.png)
this is equivalent to:
![y\text{ = -3x +13}](https://img.qammunity.org/2023/formulas/mathematics/college/v38orq95t0tl6lbmk5mnanevdfi4kiqr58.png)
Then the above equation is in the form y = mx +b.
3) Let the following equation:
![0.2x\text{ + 0.3y = 0.5}](https://img.qammunity.org/2023/formulas/mathematics/college/b9jbuykx5a14l0tk05oxylhiokey82j49z.png)
subtracting to both sides of the equation the term 0.2x , we get:
![\text{ 0.3y = 0.5}-0.2x](https://img.qammunity.org/2023/formulas/mathematics/college/u0vbj614whzmgcs7i6am56kl75fv8w4gyh.png)
this is equivalent to:
![\text{ 0.3y = }-0.2x+0.5](https://img.qammunity.org/2023/formulas/mathematics/college/eltbiyzjymjczlrfyr38j1lp2gkpt47m3n.png)
now, dividing both sides of the equation by 0.3, we have that this is equivalent to:
![\text{ y = }(-0.2)/(0.3)x+(0.5)/(0.3)](https://img.qammunity.org/2023/formulas/mathematics/college/e8w750w0feevlg5j1va34kp3gl2313x251.png)
this is equivalent to:
![\text{ y = }(-2)/(3)x+(5)/(3)](https://img.qammunity.org/2023/formulas/mathematics/college/qcrwamwacgdpfxhwq0or754j9f5upsrgvf.png)
Then the above equation is in the form y = mx +b.
4) Consider the following equation:
![(1)/(4)y+3\text{ = -5x}](https://img.qammunity.org/2023/formulas/mathematics/college/1vjv6qujjcymzg3g3j525kk50phlzobpmr.png)
subtracting to both sides of the equation the number 3 , we get:
![(1)/(4)y\text{ = -5x}-3](https://img.qammunity.org/2023/formulas/mathematics/college/69pgs6o8gru5qvjebcik2sc4znb9grzfm2.png)
now, multiplying both sides of the equation by 4, we get:
![y\text{ = -20x-12}](https://img.qammunity.org/2023/formulas/mathematics/college/k4q7iu25a1iz31gnpec1g9dt89vj5vfo29.png)
Then the above equation is in the form y = mx +b.